Living with heart failure - Allie, S.; Sliwa, K. (SA Heart Journal, 2025)
Heart failure (HF) remains a global health concern affecting approximately 64.3 million people worldwide. In sub-Saharan Africa the pattern of HF is diverse and different to what is reported by the Global North, such as the relatively young age of participants reported in The Sub-Saharan African Survey of HF (THESUS-HF) study. Despite notable progress over the past 2 decades in advancing the understanding of HF in Africa, important knowledge gaps persist. These include outdated data on access to care and a lack of information regarding the incidence, aetiology, availability, and affordability of HF medications. The THESUS-HF II study, under the umbrella of the Pan African Cardiac Society is currently underway. So far 16 countries participate, and more than 1 400 patients have been recruited (Figure 1). It is expected that the study will provide more understanding into access to care as well as comorbidities, risk factors and outcomes of HF.